2005
DOI: 10.1002/ijc.21206
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HDMX‐S (or MDM4) mRNA splice variant overexpression and HDMX gene amplification on primary soft tissue sarcoma prognosis

Abstract: The product of the HDMX (or MDM4) gene is structurally related to the MDM2 oncoprotein and is also capable of interacting with the tumor suppressor protein p53. The aim of our study was to determine the amplification status of the HDMX gene and the expression of the HDMX mRNA (particularly that of the HDMX-S splice variant) in soft-tissue sarcomas (STS). Patients with STS were evaluated for the status of HDMX gene amplification (n 5 66) and HDMX-S mRNA expression (n 5 57) within their tumors. DNA, total RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 21 publications
6
91
2
Order By: Relevance
“…38 and that is expected to correlate with a more aggressive behavior. In line with recent sarcoma genetic data, 22 all of the analyzed WD/DD LPS were disomic for MDMX.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…38 and that is expected to correlate with a more aggressive behavior. In line with recent sarcoma genetic data, 22 all of the analyzed WD/DD LPS were disomic for MDMX.…”
Section: Discussionsupporting
confidence: 84%
“…12 Finally, there are no published data regarding the presence of MDMX-S in WD/DD LPS, although it has been identified in 70% of soft tissue sarcomas. 22 We have now found that MDM2 and full-length MDMX, together with their MDM2-B and MDMX-S isoforms, are expressed and translated in WD/DD LPS surgical specimens. Furthermore, the findings of our in vitro and in silico experiments show that they contribute differently to Nutlin-3A sensitivity and resistance.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Aneuploid DNA content has been correlated with a poorer prognosis [70]; proliferative activity, as reflected by S-phase fraction, silver staining for nucleolar organizer regions, Ki-67 and PCNA, has also been correlated with survival [71][72][73][74]. The expression of oncogenic and tumor-suppressor proteins, such as Bcl-2, MDM2, retinoblastoma gene product and p53, are some of the more well-published molecules that have been associated with prognosis in soft-tissue sarcoma [24,[75][76][77][78].…”
Section: Nonmorphologic Prognostic Factorsmentioning
confidence: 99%